Water Quality Evaluation and Comparison of Provincial Assessment Sections Based on Evaluation Method by Entropy-Weighted Cloud Model - MA Congcong; LIU Dengfeng; HUANG Qiang; YANG Zhiyong; PAN Baozhu; LIN Mu (Renmin Zhujiang)
As the water environment system is random and fuzzy,and the cloud model proposed in the 1990s can flexibly realize the conversion of data and concepts,the model is gradually applied in water quality evaluation.Water quality evaluation is essentially a multi-attribute classification problem,and the Euclidean distance can well characterize the multi-attribute problem,which is also gradually applied in water quality evaluation.To compare the advantages and disadvantages of the variable-weighted Euclidean distance method and the evaluation method by the entropy-weighted cloud model in water quality evaluation,we utilize the water quality monitoring data of three major rivers in Shaanxi Province in 2020,i.e.,Weihe River,Hanjiang River,and Danjiang River.Specifically,we evaluate the environmental quality of surface water in 40 cross-sections of the three rivers using the above two methods.The results reveal that the water quality in the study area is good,and the water quality in more than 70% of the sites reaches Class III.The seriously polluted cross-sections are mainly located in the tributaries of Weihe River,and the main pollutants are chemical oxygen demand (COD) and ammonia nitrogen.